Saúde mental na atenção básica: Limites e possibilidades de uma prática em comum - Castro, Marília Moura de (2016)
The changes in the attention to mental health in Brazil was intensified in the 90s when it started the movement of Brazilian Psychiatric reform which has a reorientation of a new caring model and a new social place for madness as its main focus. This new logic in mental health allowed the change of Psychiatric paradigm to the psychosocial paradigm. This represents a political, technological and ideological breakthrough. From this paradigm shift and practices reorientation, investments in community practices have been considered a priority for public health policies that establish the scope of primary care as the setting for the implementation of the principles of SUS and RPB. From this perspective operate the primary care services in SUS, represented by the Estratégia Saúde da Família (ESF). The fact that the ESF teams are entered in the territories increases the therapeutic work of professionals with regard to attention to users, for its proximity to the families. This study aimed at analyzing the care strategies carried out by mental health professionals of the Estratégia Saúde da Família (ESF) in João Pessoa/PB. It is characterized as an action-research aiming at the practice and knowledge to solve problems and the proposed actions to assist the ones involved in their transformative activity.The study took place at a health team in João Pessoa / PB, were it was conducted with those professionals the following procedures for data collection: focus groups, visits, workshop, varying the number of participants for each activity.For the data analysis it was done content Analysis. It was found that professionals use various strategies to cope with the demands of mental health of the territory, specifically: PTS, Genogram, listening, bonding, welcoming, home visits, desmedicalization, etc. The strategies with highest potential in the team were: listening, PTS, NASF support. Some difficulties in realizing the care in mental health were identified such as: the lack of training, excess in the demand and weakness in the health care network. That way, we can conclude that ESF has great potential to deal with mental health demands, however there are still many limits to this practice, being necessary to offer courses and qualifications as well as the completion of an ongoing process of building a care guided by the logic of deinstitutionalization, the autonomy of the subjects and in their lives.